A public code for astrometric microlensing with contour integration. Issue 1 (14th May 2021) - Bozza, Valerio; Khalouei, Elahe; Bachelet, Etienne
ABSTRACT: We present the first public code for the calculation of the astrometric centroid shift occurring during microlensing events. The computation is based on the contour integration scheme and covers single and binary lensing of finite sources with arbitrary limb darkening profiles. This allows for general detailed investigations of the impact of finite source size in astrometric binary microlensing. The new code is embedded in version 3.0 of vbbinarylensing, which offers a powerful computational tool for extensive studies of microlensing data from current surveys and future space missions.